DISCOURSE OF INDONESIAN MEN’S BODY FIGHT IN MEN’S FITNESS CONTEST - Teguh Dwi Putranto; Rahma Sugihartati; Santi Isnaini; Suko Widodo; Erica Monica Abao Garcia (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
The men body is not only seen as a body. Currently the men body has been exploited by capitalism which rivals the popularity of the women body which is usually exploited through beauty contests. The men body, which is disciplined by fitness products, has now ventured into men's fitness contests, one of which is The New L-Men of The Year which has been transformed from L-Men of The Year. This is one of the annual fitness contests for Indonesian men which was stopped in 2014, and then re-held in 2018. This research seeks to unravel the discourse behind The New L-Men of The Year using critical discourse analysis method by van Dijk. The unit of analysis for this research is online news on fimela.com related to the fitness contest The New L-Men of the Year 2018 period. The results showed that the discourse that emerged in the men's fitness contest through The New L-Men of The Year was a discourse on a healthy lifestyle. This healthy lifestyle is transmitted by the winner of The New L-Men of The Year as a health influencer who does not always highlight his six pack, but has the ability to communicate and understand the digital world as a form of persuasion of a healthy lifestyle.